Effect of aqueous extracts of some indigenous medicinal plants on sheath blight of rice (Journal of the Bangladesh Agricultural University, 2016)
Aqueous extract of some indigenous plant parts were evaluated for its efficacy to control sheath blight of rice. Six treatments were applied, viz. T1- control (water spray), T2- Tulsi (Ocientific tenuiflorum) extract (1:10), T3- Nishinda (Vitex negundu) extract (1:10), T4- Thankuni (Centella asiatica) extracts (1:10), T5- Biskatali (Polygonum hydropiper) extract (1:10) and T6- Proud (Propiconazole @ 0.2%) as a positive control. Effect of these plant extracts on percent tiller infection and percent relative lesion height of sheath blight of rice cultivar BRRI dhan 49 was determined at 55, 75 and 95 day after transplanting (DAT). Number of infected tillers per hill differed significantly among the different treatments. The highest number of infected tillers was observed in control treatment. The lowest and statistically similar number of infected tillers was found in fungicide, Proud (Propiconazole)- and Biskatali- treated plots. Reduced number of infected tillers was observed in Tulsi, Thankuni and Nishinda. Highest percent tiller infection was recorded in control and lowest percent tiller infection was recorded in Proud and Biskatali, which were statistically similar. Nishinda, Tulsi and Thankuni had reduced tiller infection in compare to control. Percent reduction of tiller infection over control was achieved by proud followed by Biskatali. The highest lesion height was observed in control and lowest lesion height was found in Proud followed by Biskatali. The highest percent relative lesion height was recorded in control followed by Thankuni. The lowest percent relative lesion height was recorded in Proud preceded by Biskatali. Highest percent reduction of relative lesion height over control was achieved by proud followed by Biskatali. Thus, plant extracts of Biskatali, Tulsi, Nishinda and Thankuni are effective to control sheath blight of rice. Among the plant extracts, Biskatali showed highest control of sheath blight disease of rice.J. Bangladesh Agril. Univ. 14(1): 7-12, June 2016